Production Plan for Wafer Stick Department Using Linear Programming - Yudoko, Gatot; Mirzanti, Isti R (Jurnal Manajemen Teknologi, 2009)
Wafer Stick Department of a company located in Bekasi, Indonesia, produces 18 kinds of cookies daily to serve both domestic and foreign markets. All these products had the same production processes, namely warehousing of raw materials, mixing, drying, and packing. This department had its own production plan and would like to know whether the existing plan was a good plan or not. The purpose of this paper is to propose linear programming as a technique that can be used to formulate daily production plan for the Wafer Stick Department. In this paper, we compare the maximum profit obtained by the linear programming to that of the existing plan. The comparison was based on a five week schedule.Observations to the plant, especially at the Wafer Stick Department, interviews with the production planner of the Wafer Stick Department as well as the Marketing Department, and the collection of the required data were used to characterize parameters of the linear programming, namely profit contribution of each product, machine capacity, technological coefficients representing resource usage for producing each type of product in each machine, and other necessary requirements. We used WinQSB to solve our linear programming model which resulted in a feasible and optimal solution with a total profit for the five weeks 2.47 billion rupiahs and this is 0.73 billion rupiahs higher than the use of the existing production schedule.Keywords: production planning, linear programming, wafer stic